2012
DOI: 10.1371/journal.pone.0053281
|View full text |Cite
|
Sign up to set email alerts
|

LAT Region Factors Mediating Differential Neuronal Tropism of HSV-1 and HSV-2 Do Not Act in Trans

Abstract: After HSV infection, some trigeminal ganglion neurons support productive cycle gene expression, while in other neurons the virus establishes a latent infection. We previously demonstrated that HSV-1 and HSV-2 preferentially establish latent infection in A5+ and KH10+ sensory neurons, respectively, and that exchanging the latency-associated transcript (LAT) between HSV-1 and HSV-2 also exchanges the neuronal preference. Since many viral genes besides the LAT are functionally interchangeable between HSV-1 and HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Therefore, we coinfected AMTC with HSV-1/LAT2 and HSV-2-green fluorescent protein (GFP) (12) and assayed the pattern of productive infection of each virus. Only 5% of KH10ϩ neurons were productively infected with HSV-1/LAT2, similar to percentages with either HSV-2 or HSV-2-GFP alone ( Fig.…”
mentioning
confidence: 99%
“…Therefore, we coinfected AMTC with HSV-1/LAT2 and HSV-2-green fluorescent protein (GFP) (12) and assayed the pattern of productive infection of each virus. Only 5% of KH10ϩ neurons were productively infected with HSV-1/LAT2, similar to percentages with either HSV-2 or HSV-2-GFP alone ( Fig.…”
mentioning
confidence: 99%
“…To determine if HSV-1 and HSV-2 could reactivate from individual autonomic neurons, mice were infected with HSV-1 or HSV-2 viruses that express a VP26-GFP fusion protein during replication. VP26, expressed by a late gene, is a small capsid protein that decorates the outer surface of the mature capsids, bound to VP5 (20)(21)(22); previous studies have demonstrated that the HSV VP26-GFP reporter viruses effectively represent productive infection (3,5). Twenty-one days postinfection, when the viruses had established latency, TG, SCG, and CG were removed from infected mice, cultured, and observed for viral reactivation, visualized by expression of GFP in individual neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Sensory neurons recognized by monoclonal antibody Fe-A5 (A5ϩ) limit productive HSV-1 infection (3,4). In contrast, sensory neurons bound by the monoclonal antibody KH10 or isolectin IB4 (IB4ϩ) limit productive infection of HSV-2 (3)(4)(5). Similar percentages of these nonoverlapping populations of sen-sory neurons are found in TG (10 to 12%) and DRG (13 to 15%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Observations obtained with mouse neurons point to the relevance of the differential expression of neurotrophic factor receptors in different neurons and its effect on the establishment of HSV latency [22]. Indeed, the differential expression of neurotrophic factor receptor and other neuronal markers in mouse neurons seems to be linked to the preference of HSV-1 or HSV-2 to establish latency in distinct subpopulations of mouse sensory neurons [27,28]. In particular, NGF dependent neurons seem to support HSV-2 productive infection, but not latency, whereas the contrary is true for HSV-1 [27].…”
Section: Discussionmentioning
confidence: 99%